Composition of Flavorings for Home-Made Alcoholic Beverages - Andrey V. Oberenko; Sergei V. Kachin; Sergei A. Sagalakov; Artem D. Yakovlev; Natalia A. Kozel (Техника и технология пищевых производств)
Flavorings give commercial alcoholic beverages a recognizable sensory profile. Their quality, chemical composition, acceptable levels, and control methods are standardized by the state. For home-made alcoholic beverages, the market offers a wide range of flavorings that imitate popular brands. However, their composition is seldom labelled, and their quality control methods remain unknown. The research objective was to study the component composition of imitation flavorings in order to develop appropriate analytical measurement protocols. The research featured flavorings of different brands that imitate flavor profiles of cognac, chacha, tequila, brandy, gin, and liqueur. It included a FT-801 Fourier spectrometer (SPF SIMEX, Russia) with SIMEX attachment (Russia) for attenuated total internal reflectance, as well as a Crystal-5000.2 gas chromatograph (Russia) with a TR-5MS column and an ISQ quadrupole mass spectrometric detector (Thermo Fisher Scientific, USA). To detect the solvents (carriers), 0.050 cm3 of each sample solution was mixed with 10 cm3 of methanol. To detect the flavoring agent, the sample solutions were pre-extracted with trichloromethane (chloroform). The obtained IR-NIR spectra were processed using the OMNIC software; the mass spectra were processed with NIST MS Search 2.0 (NIST, USA). The research revealed the following data on the nature of solvent carriers and flavoring agents. Propylene glycol, glycerol, and triacetin acted as solvents (carriers). As few as 1–5 substances were responsible for the sensory profile, but they made up ≥ 70% of the total composition. The cognac flavoring of the Elix brand contained 4-hydroxy-3-methoxybenzaldehyde (vanillin, 78.5%); the chacha flavor (Alcotec) was provided by 3,7-dimethyl-1,6-octadien-3-ol and methyl-2-aminobenzoate (94.4%); the brandy taste (Alcotec) was imitated by vanillin and ethyl laurate (81.7%); the tequila flavoring (Alcostar) contained 3-methyl-1-butanol, ethyl decanoate, ethyl laurate, and vanillin (73.7%); the gin-tonic flavor (Etol) resulted from a combination of phenylmethanol, 3,7-dimethyl-1,6-octadien-3-ol, (1R)-1-isopropyl-4-methyl-3-cyclohexen-1-ol, and 2-(4-methyl-3-cyclohexen-1-yl)-2-propanol (83.5%). None of the artificial additives had the same flavoring agents in the same relative content as the original drinks. In this study, a combination of FTIR-ATR spectrometry and GC-MS spectrometry with subsequent mathematical processing provided comprehensive information on the chemical composition of flavoring agents that could be used to assess their sensory profiles, food safety, and authenticity.